1999
DOI: 10.1002/pen.11492
|View full text |Cite
|
Sign up to set email alerts
|

Blends of thermoplastic polyurethane and maleic‐anhydride grafted polyethylene. I: Morphology and mechanical properties

Abstract: Thermoplastic polyurethane elastomers (TPU) and polyethylene (PE) form immiscible blends with an extremely low compatibility. In order to improve the dispersion, stability, and properties of these blends, polyethylene was grafted with maleic anhydride (PE‐g‐MA). Subsequently, it was blended with a commercial polyester ‐ type TPU in a twin‐screw extruder. With PE‐g‐MA as blend component, the particle size was dramatically reduced in comparison with PE. Coalescence was significantly reduced and the increase in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…any researchers have shown that the size of the M dispersed phase in polymer blends increases with the increase of the dispersed phase fraction (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, it has been also reported that at high dispersed phase fractions, particle sizes of blends with high viscosity ratio (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…any researchers have shown that the size of the M dispersed phase in polymer blends increases with the increase of the dispersed phase fraction (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, it has been also reported that at high dispersed phase fractions, particle sizes of blends with high viscosity ratio (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the enough long and flexible molecular chains, EPDM chains can entangle among themselves and also with the TPU chains. This entanglement impedes severely with the flow of the melt at low shear rates, and consequently, the viscosity becomes higher 33. However, the disentangling effect is much greater that entangling one at high shear rates, because the repulsion between EPDM chain and the hard segments of TPU arises from incompatibilizaton of both of them 34.…”
Section: Resultsmentioning
confidence: 99%
“…The crosslinking of polyethylene can be avoided by using technologies of pre-irradiation and reactive extrusion grafting (12). Grafting of the nonsaturated monomers containing functional groups to olefin polymer macromolecules aimed to create functional polymers is widely applicable in present-day chemistry, chemical technologies, and polymer materials' science (13)(14)(15)(16)(17). The monomers often used for grafting copolymerization are maleic anhydride, acrylic acid, and its derivatives and so on (18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%